L'évaluation du Plan Réussite en Licence : quelles actions pour quels effets ? Analyse sur les résultats des étudiants en première année universitaire - Sophie Morlaix; Cathy Perret (Recherches en Éducation)
The first cycle at the university is characterized by a poor internal effectiveness. In 2007, the public authorities announce the "Plan réussite en Licence" (PRL), to reduce the rate of failure in first year. This article aims to evaluate the effectiveness of the actions of PRL on results of the first-year students. The originality of this research is due not only to innovative character of the analyses carried out, but too to multitude of the factors of success taken into account simultaneously, some referring to the characteristics students, others with the characteristics of the context, such as those relating to the PRL. This analysis is carried out on six troops of students in the first year and proceed in a comparative way, the first three troops haven't profited from actions of PRL. After having clarified our methodological choices, we have the results of the econometric models carried out. The latter underline the difficulties of apprehending a positive effect of the actions of the PRL.